Answer:
See attached photo
Step-by-step explanation:
<span>So we have a problem with two unknows and one equation. We have to express one over the other like this: 7a - 2b = 5a + b. First we separate one kind on the left side and the other kind on the right side: 7a - 5a = b + 2b. Then: 2a = 3b. Now we divide both sides by 2 and get: a= 3b/2.</span>
Answer: 3.5, 4.5, 9.5, 3.5
Step-by-step explanation:
Look at the image below to see where A, B, C, and D are.
A + B = 8
B + D = 8
A + C = 13
C - D = 6
we can see that A + B = 8 and D + B = 8, so A = D
substitute this into A + C = 13 to get D + C = 13
from D + C = 13 we can get D = 13 - C
plug this into C - D = 6 to get C - (13 - C) = 6
2C - 13 = 6
2C = 19
C = 9.5
Now we can find D = 13 - C = 13 - 9.5 = 3.5
D = 3.5
Now we can find A = D = 3.5
A = 3.5
Now we can find B from A + B = 8
B = 8 - A = 8 - 4.5 = 4.5
B = 4.5
Answer:
0.6x+y=24.6
Step-by-step explanation:
y-y1=m(x-x1)
y-24=-0.6(x-1)
y=-0.6x+0.6+24
y=-0.6x+24.6
y-(-0.6x)=24.6
y+0.6x=24.6
0.6x+y=24.6
Answer:B
Step-by-step explanation:
The curve cuts the x-axis at points x=3/2 and x=3
F(x)= ((x-3/2)(x-3)
=x2-3x-3x/2+9/2
2x2-6x-3x+9
=2x2-9x+9